Macular thickness in patients with pseudoexfoliation syndrome after uneventful phacoemulsification - V. V. Potemkin; S. Yu. Astakhov; Siaoyuan Van; À. R. Potemkina; L. К. Anikina (Российский офтальмологический журнал, 2022)
To evaluate macular thickness in patients with pseudoexfoliation syndrome (PXS) after phacoemulsification.   Materials and methods. 30 patients with PXS (mean age 74.05 ± 5.21 years) and 31 age-matched patients (mean age 71.35 ± 7.51 years) without PXS (control group) were examined to assess macular thickness, which was measured by optical coherence tomography before phacoemulsification, 2 weeks, 2 and 6 months after it.   Results. A significant increase in retinal thickness was noted in patients of both groups in parafovea 2 weeks after phacoemulsification, in parafovea and periphovea after 2 months, and in parafovea after 6 months. At 2 months after surgery, in patients with PXS, the thickness o f the retina in the fovea and perifovea was significantly higher than in the control group; at other times, no difference was observed between the groups.   Conclusion. PXS does not affect macular thickness after phacoemulsification if no intraoperational or postoperational complications took place.